2015
DOI: 10.3390/agriculture5020267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Date Palm Cultivar, Particle Size, Panel Density and Hot Water Extraction on Particleboards Manufactured from Date Palm Fronds

Abstract: Abstract:The objective of this work was to evaluate some of the important physical and mechanical properties of particleboard panels manufactured from three different cultivars of date palm (Phoenix dactylifera) fronds, namely Saqui, Barhi and Sukkari. Experimental panels were manufactured from hot water extracted and non-extracted, and fine and coarse particles of the raw material under two target panel densities of 650 and 750 kg/m 3 . Bending properties and internal bond strength, along with dimensional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 29 publications
4
18
0
2
Order By: Relevance
“…Of the three board manufacturing variables, the particle size affects density, MOR, MOE and IB; the pressing time affects MOR, IB, TS and WA; and the pressing cycle affects MOR, MOE and IB. The particle size for manufacturing the boards has become the most important factor in the tests performed by the investigators, and it can be concluded that better properties are achieved with a smaller particle size [46], as shown in this work.…”
Section: Discussionsupporting
confidence: 60%
“…Of the three board manufacturing variables, the particle size affects density, MOR, MOE and IB; the pressing time affects MOR, IB, TS and WA; and the pressing cycle affects MOR, MOE and IB. The particle size for manufacturing the boards has become the most important factor in the tests performed by the investigators, and it can be concluded that better properties are achieved with a smaller particle size [46], as shown in this work.…”
Section: Discussionsupporting
confidence: 60%
“…Their results showed a large increase in MOE, satisfactory values of MOR and IB, and a low TS value, probably due to the nature of the curing resin. Hegazy and Ahmed and Hegazi et al [14,15] studied the influence of density on the strength of panels produced with date palm fibers at 140 • C for 10 min and 160 • C for 8 min with the same resin dose. Better strength (MOR, MOE and IB) was achieved in both cases with higher densities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted focusing on the manufacturing of building materials using different palm residues. Particleboard with synthetic adhesives and different manufacturing procedures have been studied using fibers or chips of date palm [7][8][9][10][11][12][13][14][15], washingtonia palm [5,[16][17][18], and canary palm [19][20][21]. Other studies have been performed using date palm pruning waste as a reinforcement in concrete [22][23][24], in gypsum [25], and in the manufacturing of different composites [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Le bois fibreux de la palme est utilisé comme une alternative aux déchets de bois classique dans la fabrication des différentes plaques de bois industriel (MDF, HDF, LDF…). Cette technique est utilisée par nombreux fabricants industriels dans le monde [36][37][38]. D'autre part, les fibres extraites du bois fibreux de palme attirent l'intérêt des chercheurs pour être utilisés comme renfort dans les matériaux composites [39][40][41].…”
Section: Introductionunclassified